Gastrointestinal candidiasis in a murine model of severe combined immunodeficiency syndrome. - Narayanan, R (1991)
A murine model of severe combined immunodeficiency syndrome (scid mice) affords an opportunity to study the interaction of Candida albicans with a host lacking functional B- and T-cell mechanisms. We have previously reported no significant difference in yeast recovery after intravenous challenge of BALB/c mice and scid mice with C. albicans (S. Mahanty, R.A. Greenfield, W.A. Joyce, and P.W. Kincade, Infect. Immun. 56:3162-3166, 1988). In this study, we evaluate the course of gastrointestinal candidiasis after a single oral challenge with C. albicans. BALB/c and scid mice received H2O containing 10(6) C. albicans per ml for 16 h. Half the mice of each strain continuously received H2O containing 1 mg of tetracycline per ml. Stool samples were cultured for yeast twice weekly until they were negative three consecutive times or positive for 8 weeks. Mice were then sacrificed for quantitative cultures of liver, spleen, and kidneys. At eight weeks postinoculation, 2 of 13 BALB/c mice, 0 of 14 BALB/c mice receiving tetracycline, 6 of 12 scid mice, and 8 of 13 scid mice receiving tetracycline had positive stool cultures (P less than 0.05, likelihood ratio chi-square). Quantitative recovery of yeasts from stools was also higher in the scid mice. Cultures of liver, spleen, and kidneys wer negative in all BALB/c mice and essentially all negative in scid mice; a single colony was isolated from the kidney of one scid mouse and the liver of another scid mouse. We conclude that B cells and/or T cells and their products are important in gastrointestinal colonization with C. albicans but that even in their absence, dissemination of infection from the gastrointestinal tract does not consistently occur. Thus, other aspects of host defense must be critical in containing gastrointestinal Candida colonization.